Analysis and reduction of stimulated raman scattering in DWDM fibre optic communication system - Zakaria, Salmi (2013)
Stimulated Raman scattering effect is one of the Non linear effects in Dense wavelength Division Multiplexed (DWDM) Fibre Optic communication system. The effect of Stimulated Raman Scattering causes power to be transferred from lower wavelength channel to higher wavelength channel. In the long haul transmission system, Dense Wavelength Division Multiplexing is a possible technique to use. In addition, long haul transmission level power and optical amplifier are needed to be considered. Feeding the high power to the fiber can also activate the effect of nonlinearity like Stimulated Raman Scattering (SRS). SRS effects aredecrease the peak power, decrease the OSNR, andoptical crosstalk andbut increase bit errors is the main destructive phenomena in high data rate optical communication systems.This thesis analyses the effect of SRS in DWDM fibre optic communication system on the power distribution of 8x10Gbps and 16x10Gbpsafter propagates along 25 km, 50 km, 75 km and 100 km along single mode fibre optic cable. SRS effect is studied for various power levels of individual channels which are simulated using Optisystem 8.0 in order to obtainthe effect of SRS like optical spectrum after transmission through the fibre optic cable. SRS effect is reduced by using backward Raman amplifier. The performance results are evaluated in term of eye diagram and bit error rate BER) using a single pump with 1427 nm wavelength and different pump power. An 8 channel DWDM fibre optic communication system with below than 10mW input power and 25 km fibre optic length; and 8 channel has no effect of SRS.